2020
DOI: 10.3390/en13164156
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity between Combined Heat and Power Systems, Solar PV and Hydropower at a District Level: Sensitivity to Climate Characteristics along an Alpine Transect

Abstract: Combined heat and power systems (CHP) produce heat and electricity simultaneously. Their resulting high efficiency makes them more attractive from the energy managers’ perspective than other conventional thermal systems. Although heat is a by-product of the electricity generation process, system operators usually operate CHP systems to satisfy heat demand. Electricity generation from CHP is thus driven by the heat demand, which follows the variability of seasonal temperature, and thus is not always correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The application of district heating and cooling (DHC) technologies is acknowledged as a promising solution to the supply of temperature conditioning in buildings [113], which can effectively save energy and reduce emissions. For decarbonized and sustainable development, DHC is an attractive solution with the application of low-quality heat resources, both from renewable sources (such as solar PV panels [114], geothermal energy [115], wind [116], biomass [117] and hydropower [118]) and industrially generated waste heat [119]. The evaluation of reliable energy sources for different DHC sectors is quite a challenge, since it is difficult to describe the actual energy profiles in specific districts [120].…”
Section: Development Of District Heating Systemmentioning
confidence: 99%
“…The application of district heating and cooling (DHC) technologies is acknowledged as a promising solution to the supply of temperature conditioning in buildings [113], which can effectively save energy and reduce emissions. For decarbonized and sustainable development, DHC is an attractive solution with the application of low-quality heat resources, both from renewable sources (such as solar PV panels [114], geothermal energy [115], wind [116], biomass [117] and hydropower [118]) and industrially generated waste heat [119]. The evaluation of reliable energy sources for different DHC sectors is quite a challenge, since it is difficult to describe the actual energy profiles in specific districts [120].…”
Section: Development Of District Heating Systemmentioning
confidence: 99%
“…One of the ideas for the energy-and environmentally efficient use of fossil fuels is cogeneration systems [27], where heat and electricity are produced simultaneously in one process. This concept has been reported as beneficial [28,29]. Heat obtained in the electricity production process can be treated as waste [27], and its useful use increases the energy efficiency of the system [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…The complementarity concept was not only studied for solar and wind energy resources but also for other technologies such as a combined heat and power station (CHP), run-of-the-river (RoR) and large-scale hydropower. Puspitarini et al [17] investigated the combination of solar photovoltaic panels, run-of-the-river and a combined heat and power station in a 100% renewable energy mix scenario. This study was conducted for seventeen districts in north-eastern Italy, where its results indicated that integration of the CHP system is a promising solution to strengthen the energy balance and increase load satisfaction.…”
Section: Introductionmentioning
confidence: 99%